#### Answer

$4$

#### Work Step by Step

$\sum ^{\infty }_{i=1}3\left( \dfrac {1}{4}\right) ^{i-1}=\dfrac {a_{1}}{1-r};a_{1}=3\times \left( \dfrac {1}{4}\right) ^{1-1}=3;r=\dfrac {1}{4}\Rightarrow S_{\infty }=\dfrac {3}{1-\dfrac {1}{4}}=4$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$4$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.